Non-governmental organizations and political institutionalization in the Philippines - Clarke, Gerard (Philippine Journal of Public Administration, 1994)
The Philippine Non-Governmental Organization/People's Organization (NGOIPO) community, one of the largest and best organized in the developing world, has become an important actor in Philippine politics. Yet the political and organizational dynamics of the NGO/PO community have been subjected to little in-depth scrutiny to date. This article analyzes the manner in which Philippine NGOs organize themselves, both individually and collectively. It concludes that despite the significant new opportunities since 1986, NGO effectiveness in the political arena is undermined by weaknesses which the article traces to the process of internal political institutionalization which NGOs/POs are currently undergoing.